Redondoviridae, a Family of Small, Circular DNA Viruses of the Human Oro-Respiratory Tract Associated with Periodontitis and Critical Illness - Abbas, Arwa A; Taylor, Louis J; Dothard, Marisol I; Leiby, Jacob S; Fitzgerald, Ayannah S; Khatib, Layla A; Collman, Ronald G; Bushman, Frederic D (Cell host & microbe, 2019)
The global virome is largely uncharacterized but is now being unveiled by metagenomic DNA sequencing. Exploring the human respiratory virome, in particular, can provide insights into oro-respiratory diseases. Here, we use metagenomics to identify a family of small circular DNA viruses-named Redondoviridae-associated with human diseases. We first identified two redondovirus genomes from bronchoalveolar lavage samples from human lung donors. We then queried thousands of metagenomic samples and recovered 17 additional complete redondovirus genomes. Detections were exclusively in human samples and mostly from respiratory tract and oro-pharyngeal sites, where Redondoviridae was the second most prevalent eukaryotic DNA virus family. Redondovirus sequences were associated with periodontal disease, and abundances decreased with treatment. Some critically ill patients in a medical intensive care unit were found to harbor high levels of redondoviruses in respiratory samples. These results suggest that redondoviruses colonize human oro-respiratory sites and can bloom in several human disorders.